Validasi Intervensi Psikologis: “Positive Parenting Brief Family Therapy” - Khair, Nurul Fadhilah; Farid, Risanita Fardian; Angguna, Welan Mauli (ANFUSINA: Journal of Psychology, 2022)
The parenting style applied by both parents has a big influence on the child's development. The low interaction between one or both parents in parenting has an impact on the poor attachment between parent and child. Dysfunctional parenting causes children to have low psychological well-being, less optimal and effective maternal care also has a significant impact on the child's mental and emotional development. Good parenting will reduce the damage to the child's social skills and he can be accepted by his peer environment. This study aims to increase information and knowledge about positive parenting through positive parenting education training. The training module is structured around the positive parenting principles coined by John Gray. The research module was prepared based on the Russell method with a focus on content and empirical validation tests. The content validation test resulted in Aiken V values moving between 0.71 to 0.94 with a mean of 0.78, while the empirical validation showed a decrease in the pretest and posttest scores on the dysfunctional parenting scale in the experimental group. Based on the legibility test, this module can be an alternative option to be given to parents in order to be able to implement positive parenting in the family.Keywords: Positive Parenting, Mother's Care, Mother's involvement